Massage impairs postexercise muscle blood flow and "lactic acid" removal - Wiltshire, E. V.; Poitras, V.; Pak, M.; Hong, T.; Rayner, J.; Tschakovsky, M. E. (Medicine & Science in Sports & Exercise, 2010)
Purpose: This study tested the hypothesis that one of the ways sports massage aids muscle recovery from exercise is by increasing muscle blood flow to improve "lactic acid" removal.